Neotropical Insect Galls 2014
DOI: 10.1007/978-94-017-8783-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Neotropical Insect Galls: Status of Knowledge and Perspectives

Abstract: This book seeks to expose the reader to those studies which have made the greatest contribution to the body of knowledge surrounding the insect galls in the Neotropical region. There seems to be countless groups of researchers working both in Brazil and in other tropical regions of the Americas. The chapters presented here report the diversity of studies conducted to date as well as indicate the quality of the studies in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…High-altitude grasslands 'campos de altitude' are mosaics of different vegetation types with a predominance of shrub species, especially those belonging to the genus Baccharis (Asterales: Asteraceae) (Safford 1999a(Safford ,b, 2001(Safford , 2007. According to Fernandes et al (1996Fernandes et al ( , 2014a, Baccharis may be the most species-rich genus in the Neotropical Region. This statement was supported by the present study, which found Baccharis to possess 40% of galling insect species, while Tibouchina (Myrtales: Melastomataceae) possessed only 12% (see Coelho et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…High-altitude grasslands 'campos de altitude' are mosaics of different vegetation types with a predominance of shrub species, especially those belonging to the genus Baccharis (Asterales: Asteraceae) (Safford 1999a(Safford ,b, 2001(Safford , 2007. According to Fernandes et al (1996Fernandes et al ( , 2014a, Baccharis may be the most species-rich genus in the Neotropical Region. This statement was supported by the present study, which found Baccharis to possess 40% of galling insect species, while Tibouchina (Myrtales: Melastomataceae) possessed only 12% (see Coelho et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since the end of the 1980s decade, studies on galling insects increased considerably in Brazil, mainly related to natural history and distribution (Fernandes et al, 2014). Nowadays, work is being carried out in all different regions of this country: North (e.g.…”
Section: Palavras-chavementioning
confidence: 99%
“…The classifi cation "unknown" was given to fully Plant-arthropod interactions are important for the structure of ecosystems, because arthropods are the most diverse and abundant plant consumers and are important prey items (McIntyre, 2000;Faeth et al, 2005;Raupp et al, 2010). Plant-galling arthropods are a good model system for assessing the response to environmental changes because of their sedentary nature and high plant host specifi city (Fernandes et al, 2014), and thus are dependent on plant host quantity and quality (Cornelissen et al, 2008). A variety of organisms can induce galls, including mites, aphids, wasps and midges (Redfern et al, 2011).…”
Section: Gall Mortalitymentioning
confidence: 99%